SIMULATION OF THE STATISTICAL CHARACTERISTICS OF THE MOLTEN METAL FLOW FOR THE EXPAND - A. N. Chichko; S. G. Lihouzov; O. A. Sachek; V. F. Sobolev; T. V. Matyushinets; O. I. Chichko (Литьë и металлургия)
Based on the simulation results distributions of the statistical characteristics of the molten metal for Widening and Narrowing gating systems with high static pressure was calculated. A comparative analysis of Widening and Narrowing gating systems with high static pressure was held. Found that only at the time of 12 sec, number of cells with high speeds for Narrowing gating system is excessed.